Water and sediments yields estimation: A case study in Bawashaswar Watershed/ Iraqi Kurdistan Region - Sarkawt G. Salar; Abdulhaq N. Mahmoud; Arsalan A. Othman (Kuwait Journal of Science)
Water flow in the seasonal streams, forms a vital supplier of water resources, particularly in arid and semi-arid areas due to its high-water supply from the precipitation during the wet season. This research aims to estimate water and sediment yields in the Bawashaswar watershed. The study area is far from Kirkuk City ~100 km. It has a semiarid climate and covers an area of 277 km2. The Bawashaswar Dam was constructed —for multi-purposes such as drinking, irrigation, livestock, and tourism— at the outlet of the watershed north of Kifri town. This study aims to give valuable data and information about water and sediment yields within the watershed of the Bawashaswar Dam and the possibility of the investment of the water for the above purposes. We integrate the Soil Water Assessment Tool (SWAT) with several data such as satellite images, Digital Elevation Model (DEM), land use, land cover, curve number (CN), daily climatic data of temperature, precipitation, and digital soil map to achieve the results. The estimated results include precipitation, evaporation- transpiration, percolation, surface runoff, water yield, loss of transport, and sediment yield. These results will support the future development plans and management of the watershed, through mitigating and minimizing the size of the ground surface degradation problems all over the study area with increasing the lifespan of the Bawashaswar Dam.